2012
DOI: 10.1037/h0093965
|View full text |Cite
|
Sign up to set email alerts
|

Does the truth come out in the writing? Scan as a lie detection tool.

Abstract: We tested the accuracy of Scientific Content Analysis (SCAN), a verbal lie detection tool that is used world-wide by federal law enforcement and military agencies. Sixty-one participants were requested to write down the truth, an outright lie or a concealment lie about activities they had just completed. The statements were coded with SCAN and with another verbal lie detection tool, Reality Monitoring (RM). RM discriminated significantly between truth tellers and outright liars and between truth tellers and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 22 publications
(40 reference statements)
5
109
0
Order By: Relevance
“…One potentially promising avenue is a newly devised verbal lie detection method: The Verifiability Approach (Nahari, Vrij, & Fisher, 2012). The Verifiability Approach is based on two aspects of deceptive strategies.…”
mentioning
confidence: 99%
“…One potentially promising avenue is a newly devised verbal lie detection method: The Verifiability Approach (Nahari, Vrij, & Fisher, 2012). The Verifiability Approach is based on two aspects of deceptive strategies.…”
mentioning
confidence: 99%
“…This does not; however, appear to get us beyond about the fifty/fifty situation in determining when someone is lying to us. Our research, as well as that of many others [6,11,12], indicates that accuracy of deception detection can be increased when we take into account the kind of detail quantity and statement quality variables described above. Now admittedly it could be a bit awkward if you are evaluating the truthfulness of someone's proclamation of love for you by pulling out a form where you rate their statement in terms of its realism, reconstructability, relevance, spatial, temporal, contextual and perceptual information.…”
Section: Short Communicationmentioning
confidence: 97%
“…A great deal of research regarding deception detection reveals that one of the primary hallmarks of true statements is the presence of specific details such as the physical space in which something occurred, the time it occurred, the things and persons present when it occurred and the relationships between the different things and persons present [6,12,13]. True statements contain this kind of rich and varied detail and it is the explicit absence of such attributes of truthful statements that are so often apparent in the lies of child molesters as well as other types of liars.…”
Section: Short Communicationmentioning
confidence: 99%
“…However, it is inevitable that variance in richness appears within truthful statements and within false statements. For example, Nahari et al (2012) reported standard deviations of 91.35 (truth tellers) and 53.60 (liars) in the number of words spoken, which were large standard deviations compared to the total number of words spoken (243.14 by truth tellers and 129.20 by liars). This implies that large variations exist between individuals in the way they provide truthful or false statements.…”
mentioning
confidence: 94%
“…Indeed, RM deception research has shown that truthful statements are typically richer than false statements, and that the RM tool distinguishes truthful from false statements at about 70% accuracy (e.g., Granhag, Strö mwall, & Landströ m, 2006;Nahari, Vrij, & Fisher, 2012;Sporer & Sharman, 2006;Vrij, 2008). However, it is inevitable that variance in richness appears within truthful statements and within false statements.…”
mentioning
confidence: 95%